Study of the lump system analysis to finding constant coefficients C and M, of the equation θ(t)=ce-mt to predicting Malaysia cockle center temperature at different heating Condition - Yavari, I.; Endan, Johari; Yusof, Yus Aniza; Ibrahim, Mohd. Nordin; Ahmad, Desa (2014)
The heat transfer over time, as well as the transmission speed are quality factors that have a direct effect on cockle’s meat texture. The results of the Lumped System Analysis under three different heating processes of cockles illustrate that the transient conductivity has a strong influence on the meat texture and quality. Thus, the heat transfer process and the time duration had a direct affect on the meat texture and quality. Temperature inside the cockle was measured for each method of heating, and the harvested data for each experimental method was compared with each other With using the heat transfer equations, the trends of heating for each method were formulated. The result of the lump system analysis on the cockles indicated that the center temperature of the cockle in the air heating system,steaming and boiling methods after 35, 7 and 4 minutes respectively reached a thermal equilibrium state with the surrounding environment temperature. Furthermore, by using the Matlab fitting application and an exponential function, three different heating processes were formalized by equation θ(t)=ce-mt finding the coefficients, C and m with 95% , confidence bounds (C= 41.63, m= 0.002792, R2 = 0. 8453), (C=76.09, m= 0.02206, R2=0.902) and (C= 74.44, m= 0.014, R2= 0.9993 respectively for the air heating, boiling, and steaming processes.